Cyfrowe kompetencje muzyczne nauczycieli edukacji wczesnoszkolnej - Schrager, Katarzyna; Pietruszka, Adam (Studia Edukacyjne, 2024)
The article addresses the topic of digital musical competencies of early childhood education teachers, emphasizing their significance and practical application in the teaching process. The study presents definitions of key concepts and discusses the role of digital technologies in education, with a focus on their implementation in music teaching. It offers the results of empirical research conducted on a group of 363 early childhood education teachers from randomly selected primary schools in Poland, who completed a detailed questionnaire assessing their skills and the extent of using modern digital tools such as notation software, audio recording and editing programs, and interactive music applications. The findings revealed both the widespread use of basic multimedia technologies and significant gaps in more advanced digital competencies. The article concludes with the formulation of findings and recommendations regarding the need for the development of training programs and systematic education on the use of digital technologies, which could contribute to enhancing the quality of music education at the early childhood level.